Answer:
Step-by-step explanation:
We would apply the formula for determining compound interest which is expressed as
A = P(1+r/n)^nt
Where
A = total amount in the account at the end of t years
r represents the interest rate.
n represents the periodic interval at which it was compounded.
P represents the principal or initial amount deposited
From the information given,
P = $470
r = 6% = 6/100 = 0.06
n = 1 because it was compounded once in a year.
Therefore, the equation used to determine the value of his bond after t years is
A = 470(1 + 0.06/1)^1 × t
A = 470(1.06)^t
Hey Dammy17,
Ok so what we need to do is "plug in" 2oz for x in the equation,
So, 0.6 (2) + 11 =
0.12 + 11= 11.12 oz is the finishing weight.
An adaptation that might<span> help a plant survive in an environment with cold winters is developing pine needles or losing leaves during such periods of time.</span>
Answer:
48
Step-by-step explanation:
Answer:
Step-by-step explanation:
3x – y + 2z = 6 - - - - - - - - - 1
-x + y = 2 - - - - - - - - - - - - -2
x – 2z = -5 - - - - - - - - - - - -3
From equation 2, x = y - 2
From equation 3, x = 2z - 5
Substituting x = y - 2 and x = 2z - 5 into equation 1, it becomes
3(y - 2) – y + 2z = 6
3y - 6 - y + 2z = 6
3y - y + 2z = 6 + 6
2y + 2z = 12 - - - - - - - - - 4
3(2z - 5) – y + 2z = 6
6z - 15 - y + 2z = 6
- y + 6z + 2z = 6 + 15
- y + 8z = 21 - - - - - - - - - - 5
Multiplying equation 4 by 1 and equation 5 by 2, it becomes
2y + 2z = 12
- 2y + 16z = 42
Adding both equations
18z = 54
z = 54/18 = 3
Substituting z = 3 into equation 5, it becomes
- y + 8×3 = 21
- y + 24 = 21
- y = 21 - 24 = - 3
y = 3
Substituting y = 3 into equation 2, it becomes
-x + 3 = 2
- x = 2 - 3 = -1
x = 1